Effects of dielectric barrier discharge plasma modification on surface properties of tropical hardwoods at low pressure - Pabelina, K. G. (2017)
The study investigated the use of dielectric barrier discharge (DBD) for surface modification of Shorea contorta(whitelauan),Gmelina arborea(yemane) and Acacia mangium. Wood specimens were exposed to oxygen plasma at various intensities ranging from 5.8 to 46.5 kW-min m-2. Surface free energy was calculated based on contact angle measurements to determine thermodynamic changes on plasma modified wood. Surface characteristics were evaluated using attenuated total reflectance Fourier transform infrared (ATR–FTIR) spectroscopy and atomic force microscopy (AFM). Results of the study showed that plasma modification resulted in significant increase in surface free energy of the three wood species investigated. ATR–FTIR indicated that plasma- treated wood had higher surface polarity compared with untreated controls. AFM 3D image showed that oxygen plasma was capable of cleaning and etching wood surface resulting in the degradation of primary and secondary cell walls